PENGARUH PENERAPAN GREEN BANKING TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA PERIODE 2016-2021 - Asfahaliza, Adinda Nabila Putri; Anggraeni, Puspitasari Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Climate change is one of the global issues that attract public concern these days. The banking sector is inseparable from the responsibility to protect the environment even though it does not directly contribute to environmental damage. Banks can apply environmentally friendly practices in their operational activities or also called green banking. This study aims to analyze the effect of implementing green banking on the profitability of commercial banks listed on the Indonesia Stock Exchange for the period 2016-2021. The application of green banking as an independent variable is projected by the Green Banking Disclosure Index (GBDI) and green banking products consisting of the number of ATM units and the frequency of M-banking transactions. Meanwhile, profitability as the dependent variable will be projected with Return on Assets (ROA). Panel data regression analysis was used to determine the effect of the independent variable on the dependent variable. The research findings reveal that partially the number of ATM units has a positive and significant effect on ROA, while GBDI and the frequency of M-banking transactions have a negative and insignificant effect on ROA. However, simultaneous testing found that the implementation of green banking projected by GBDI, Number of ATM Units, and Frequency of M-banking Transactions had a positive and significant effect on profitability.